2022
DOI: 10.1159/000525091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Epidemiology of Amyotrophic Lateral Sclerosis in Norway: A 2-Year Population-Based Study

Abstract: Background: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects motor neurons. In Europe, disease-causing genetic variants have been identified in 40–70% of familial ALS patients and approximately in 5% of sporadic ALS patients. In Norway, the contribution of genetic variants to ALS has not yet been studied. In light of the potential development of personalized medicine, knowledge of genetic causes of ALS in a population is becoming increasingly important. The present study provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Forty‐two related papers [6, 7, 22–61] were summarized and it was found that 178 of 9814 patients with ALS/FTD carried TBK1 variants, including 95 patients carrying LoF variants and 83 patients carrying missense variants (Table S4). Therefore, a meta‐analysis was performed of the frequency of TBK1 variants reported in ALS/FTD patients (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐two related papers [6, 7, 22–61] were summarized and it was found that 178 of 9814 patients with ALS/FTD carried TBK1 variants, including 95 patients carrying LoF variants and 83 patients carrying missense variants (Table S4). Therefore, a meta‐analysis was performed of the frequency of TBK1 variants reported in ALS/FTD patients (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…First, there is significant variability in the occurrence of mutations in key ALS-related genes among different ethnic groups [ 28 ]. Specifically for the Nordic countries, there is a higher occurrence of hexanucleotide expansion mutations in the C9orf72 gene, and a geographical gradient (more prevalent in the northern regions) has been observed in Finnish and Norwegian populations [ 29 , 30 ]. However, the specific distribution of these mutations within Sweden remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…11,49 C9orf72 is the most common ALS risk gene in Norway and accounted for 6.8% of all ALS cases in a recent study. 50 We did not have genotypic information and were not able to assess possible gene-environment interactions.…”
Section: Discussionmentioning
confidence: 99%